First-principles investigation of Ra doping effects on structural, electronic, and optical properties of BaTiO3 perovskite for solar cell applications - Sonia Chahar; Krishna Kumar Mishra; Rajnish Sharma (Journal of Physics Communications)
This study investigates the properties of radium-doped barium titanate (BaTiO _3 ). Using the generalized gradient approximation (GGA) based on the Perdew–Burke–Ernzerhof (PBE) approach, the bandgap energies of pure BaTiO _3 (indirect band 1.61691 eV) and RaTiO _3 (direct band 1.63612 eV) were determined. The orbital nature of Ba, Ra, Ti, and O atoms was analyzed through density of state and projected density of state analyses for pure BaTiO _3 , RaTiO _3 , and Ra-doped BaTiO _3 (x = 0.25, 0.50, 0.75). The optical properties of these materials, including dielectric constant, susceptibility, optical conductivity, polarizability (real and imaginary), absorption coefficient, refractive index, extinction coefficient, and reflectivity, were thoroughly examined. The findings provide insights into the potential applications of these materials in solar cells, optoelectronic devices, and flexible electronic devices.